uORFs with unusual translational start codons autoregulate expression of eukaryotic ornithine decarboxylase homologs - Ivanov, Ivaylo P. (National Academy of Sciences, 2008)
In a minority of eukaryotic mRNAs, a small functional upstream ORF (uORF), often performing a regulatory role, precedes the translation start site for the main product(s). Here, conserved uORFs in numerous ornithine decarboxylase homologs are identified from yeast to mammals. Most have noncanonical evolutionarily conserved start codons, the main one being AUU, which has not been known as an initiator for eukaryotic chromosomal genes. The AUG-less uORF present in mouse antizyme inhibitor, one of the ornithine decarboxylase homologs in mammals, mediates polyamine-induced repression of the downstream main ORF. This repression is part of an autoregulatory circuit, and one of its sensors is the AUU codon, which suggests that translation initiation codon identity is likely used for regulation in eukaryotes.